1995
DOI: 10.1074/jbc.270.13.7453
|View full text |Cite
|
Sign up to set email alerts
|

An E Box Element Is Required for the Expression of the ad4bp Gene, a Mammalian Homologue of ftz-f1 Gene, Which Is Essential for Adrenal and Gonadal Development

Abstract: Ad4BP, also known as SF-1, is a cell type-specific transcription factor regulating all the steroidogenic P-450 genes. Recently, the targeted disruption of the mouse ftz-f1 gene encoding Ad4BP/SF-1 has established its essential function in both adrenal and gonadal development and sexual differentiation. As an initial step toward understanding its role in the cascade of gene activations necessary for the differentiation of the steroidogenic tissues and the sex differentiation of the gonads, we isolated and chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
69
1

Year Published

1995
1995
2010
2010

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 118 publications
(78 citation statements)
references
References 66 publications
8
69
1
Order By: Relevance
“…At later stages Pod1 expression becomes sexually dimorphic and it is found in the testis interstitium but not within the ovary [65]. Pod1 was shown to repress Sf-1 expression in tissue culture experiments [65][66][67]. Consistent with this, Pod1 deficient embryos showed an expanded Sf-1 expression domain at the boundary between the gonad and mesonephros.…”
Section: Page 7 Of 23supporting
confidence: 64%
“…At later stages Pod1 expression becomes sexually dimorphic and it is found in the testis interstitium but not within the ovary [65]. Pod1 was shown to repress Sf-1 expression in tissue culture experiments [65][66][67]. Consistent with this, Pod1 deficient embryos showed an expanded Sf-1 expression domain at the boundary between the gonad and mesonephros.…”
Section: Page 7 Of 23supporting
confidence: 64%
“…An E-box-binding site within the basal promoter of the gene is critical for SF-1 expression (Nomura et al 1995), and the transcription factor POD1/capsulin was shown to suppress SF-1 expression in the gonad through binding to the E-box (Tamura et al 2001, Cui et al 2004, while WT1 has a positive role in SF-1 expression in the developing gonad (Wilhelm & Englert 2002), similarly to the LIM homeobox gene Lhx9 (Birk et al 2000). In addition, a conserved distal enhancer in intron 6 of the Sf-1 gene is important for its VMH-specific expression (Shima et al 2005).…”
Section: An Essential Actor In Adrenogonadal Developmentmentioning
confidence: 99%
“…Alternatively, an investigation of the upstream regions of these genes encoding the factors is also necessary to understand the process. Regarding the study for the upstream direction, promoter analyses have been performed so far with the WT1 (Rupprecht et al 1994), mFtz-F1 (Nomura et al 1995, and DAX1 (Burris et al 1995;Ikeda et al 1996). The onset of the gene transcription and the sex-dependent transcription occurring in the processes of adrenal and gonadal differentiation are critical events which should be elucidated by the promoter analyses.…”
Section: (Iii) Sox9mentioning
confidence: 99%